Editorial for the Special issue on Multiple Criteria Decision Making models - Aktas, Emel; Topcu, Ilker; Kucukaltan, Berk (Emerald, 2020)
This special issue idea came to life with Prof. Ilker Topcu hosting the 25th International Conference on Multiple Criteria Decision Making in Istanbul from 16 to 21 June 2019 (https://mcdm2019.org/about/). International Society on Multiple Criteria Decision Making (MCDM) brings together academicians, professionals, researchers, students and policymakers at a bi-annual conference since 1975. MCDM 2019